2021
DOI: 10.35445/alishlah.v13i3.700
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Multiple Intelligences in Islamic Religious Education

Abstract: This qualitative research aims to determine how crucial Multiple Intelligence is in Islamic religious learning. The method in this research is a theoretical study that tries to find hypotheses by examining various research sources and online media about Multiple Intelligence. The collecting data is by gathering some literature obtained from various articles, both accredited national journals and reputable international journals. Data analysis is done by mapping from the collected data and obtaining literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Previous studies have attempted to explore the potential of MI in Islamic education. For instance, integrating MI into the Islamic school curriculum can improve the quality of learning and student outcomes (Supriatna et al, 2021). In addition, research has shown that a learning approach based on the notion of multiple intelligences can increase student motivation significantly and enhance achievement in Islamic Religious Education subjects (Syukur et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have attempted to explore the potential of MI in Islamic education. For instance, integrating MI into the Islamic school curriculum can improve the quality of learning and student outcomes (Supriatna et al, 2021). In addition, research has shown that a learning approach based on the notion of multiple intelligences can increase student motivation significantly and enhance achievement in Islamic Religious Education subjects (Syukur et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…MI is recognised as being important in fostering holistic individual development (Armstrong, 2009;M. K. Smith, 2002), and a number of studies have investigated the implementation of MI in Islamic schools (Nurdin, 2020;Sabdaningtyas, 2019;Supriatna et al, 2021;Vadivukarasi & Gnanadevan, 2022). However, the systematic examination of the nature, distribution, and influence of these publications through bibliometric analysis remains thin.…”
Section: Introductionmentioning
confidence: 99%